1968
DOI: 10.1161/01.cir.38.6.1156
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of Hyperinsulinism and Hypertriglyceridemia in Young Patients with Coronary Heart Disease

Abstract: Fasting serum lipid levels, glucose tolerance, and immunoreactive insulin concentrations of 50 young patients with coronary heart disease (CHD) and 30 control subjects were evaluated to study the interrelationships of these metabolic factors. Abnormalities in one or more of these factors could be shown in 90% of the patients and 20% of the control subjects. Thirty-four of the 50 patients had elevated cholesterol or triglyceride levels, or both, 30 had abnormally elevated or delayed insulin responses after gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
2

Year Published

1970
1970
1997
1997

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(24 citation statements)
references
References 18 publications
1
21
0
2
Order By: Relevance
“…Bagdade, Porte, and Bierman (18) In studies of prolonged carbohydrate intake, the triglyceride concentration as measured in the fasting state in the morning, has frequently been found to correlate positively with the insulin concentration, and it has therefore been suggested that the increased secretion of insulin might stimulate the production of triglyceride (2). Furthermore, a significant positive correlation has been found between serum triglyceride and serum insulin levels in a group of young patients with coronary heart disease; reduction in the insulin levels with phenformin was associated with a decrease in the triglyceride concentration (21). There is, however, little evidence that insulin stimulates the formation of plasma triglyceride, although insulin given in vivo does restore the capacity of the perfused liver to secrete triglyceride (22) and in rat liver slices insulin has been reported to stimulate the incorporation of '4C-U-glucose into triglyceride fatty acids (23,24).…”
Section: Discussionmentioning
confidence: 96%
“…Bagdade, Porte, and Bierman (18) In studies of prolonged carbohydrate intake, the triglyceride concentration as measured in the fasting state in the morning, has frequently been found to correlate positively with the insulin concentration, and it has therefore been suggested that the increased secretion of insulin might stimulate the production of triglyceride (2). Furthermore, a significant positive correlation has been found between serum triglyceride and serum insulin levels in a group of young patients with coronary heart disease; reduction in the insulin levels with phenformin was associated with a decrease in the triglyceride concentration (21). There is, however, little evidence that insulin stimulates the formation of plasma triglyceride, although insulin given in vivo does restore the capacity of the perfused liver to secrete triglyceride (22) and in rat liver slices insulin has been reported to stimulate the incorporation of '4C-U-glucose into triglyceride fatty acids (23,24).…”
Section: Discussionmentioning
confidence: 96%
“…One pre-existing factor which may sway the balance in the direction of diabetes is obesity, which has a much stronger relationship in prospective studies to the incidence of diabetes than to that of CHD [31]. The common antecedents date back to adolescence or before, for association between levels of blood pressure, blood glucose and plasma lipids have been demonstrated in the young as well as in adults [32][33][34]. For both serum cholesterol and blood pressure, there is evidence of tracking of level with increasing age [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinaemia in the basal state has been described as being moderately correlated with concentrations of plasma of apo B and triglycerides. 42,43 Data regarding insulin resistance are, to-date, limited possibly because of the relationship with abdominal obesity which, per se, produces a certain degree of insulin resistance 44 that would modulate the basal state measurements.…”
Section: Discussionmentioning
confidence: 99%